O mundo público e a autogestão em Rosa Luxemburgo: uma análise do movimento das ocupações das escolas do estado de São Paulo em 2015 - Stabelini, Ana Maria (2019)
This work is the product of a conceptual study on the work of Rosa Luxemburg, and aims to contribute to the development of studies related to the conception of self-management and its articulation with conceptions of councils, public space, political self - education, as well as to discuss the self-managing character of the occupations movement of the schools of the State of São Paulo in 2015 and to discuss the possibility of its application to the design of school boards. In order to develop this thesis, some aspects are presented as fundamental: the concept of education based on political action and the possibility of autonomy and school self-government. Thus, we will consider the school not only as an organization stablished by the State, but also as a social organization, with characteristics that are intrinsic to the social groups belonging to it. The comprehension of the proposed problem will be fundamented on the conceptions of political freedom, democratic socialism, autonomy and self-government, criticism of the bureaucracy and the creation of participative organs in Rosa Luxemburg´s work. We start from the hypothesis that the self-managed councils, as conceived by Rosa Luxemburg to be spaces for the achievement of autonomy and freedom, would aim at the development of public consciousness, based on political action. In this sense, a conceptual study was carried out in the area of philosophy of education, with a view to the analysis of conceptions present in the work of Rosa Luxemburg which can explicitly give its concept of self-management. One of the elements that underpinned this study was the self-managerial experiences of the student occupations in 2015, highlighting the women's struggle and the female protagonism in the occupations. Thus, we consider this study relevant to the area of education for approaching some of its central discussions: the process of democratization of public schools, the democratic management of education and the creation of participative school councils.